2019
DOI: 10.3897/mycokeys.47.32227
|View full text |Cite
|
Sign up to set email alerts
|

Rostania revised: testing generic delimitations in Collemataceae (Peltigerales, Lecanoromycetes)

Abstract: Here, we test the current generic delimitation of Rostania (Collemataceae, Peltigerales, Ascomycota) utilizing molecular phylogeny and morphological investigations. Using DNA sequence data from the mitochondrial SSU rDNA and two nuclear protein-coding genes (MCM7 and β-tubulin) and utilizing parsimony, maximum likelihood and Bayesian phylogenetic methods, Rostania is shown to be non-monophyletic in the current sense. A new generic delimitation of Rostania is thus proposed, in which the genus is monophyletic, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
11
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(13 citation statements)
references
References 30 publications
2
11
0
Order By: Relevance
“…Our study [29] further showed that R. occultata is not monophyletic in the current circumscription. To some Fig.…”
Section: Introductionsupporting
confidence: 56%
See 4 more Smart Citations
“…Our study [29] further showed that R. occultata is not monophyletic in the current circumscription. To some Fig.…”
Section: Introductionsupporting
confidence: 56%
“…We produced 218 new sequences (Additional file 1) (53 mtSSU rDNA, 37 β-tub, 26 MCM7, 42 RPB2 5-7 and 34 RPB2 7-11) and added 26 relevant published sequences [26,29]. The concatenated matrix included 63 terminals.…”
Section: Taxon Samplingmentioning
confidence: 99%
See 3 more Smart Citations